The Role of Monoclonal Antibodies in the First-Line Treatment of Transplant-Ineligible Patients with Newly Diagnosed Multiple Myeloma - Bonello, Francesca (Pharmaceuticals (Basel), 2020)
Elderly transplant-ineligible (NTE) patients represent the majority of patients affected by multiple myeloma (MM). Elderly patients are a highly heterogeneous population, with large variability in health and functional status. Thus, choosing their optimal treatment is challenging. A wide range of first-line treatments is available, and novel-agent combinations, including monoclonal antibodies (mAbs), have recently entered clinical practice. The combination of the anti-CD38 mAb daratumumab with bortezomib, melphalan and prednisone (Dara-VMP) or lenalidomide and dexamethasone (Dara-Rd) demonstrated impressive advantages in terms of progression-free survival and minimal residual disease negativity, as compared to VMP and Rd, without safety concerns. Another anti-CD38 mAb, isatuximab, is showing encouraging results, and new isatuximab-based combinations might enter clinical practice in the future. Nevertheless, available data come from clinical trials with selected patient populations and, to date, the manageability of these regimens in real-life patients or in frail patients remains unknown. Frailty-tailored treatments, including mAbs, are under evaluation in preliminary studies. In this review, we analyze recently approved mAb-based treatments for NTE newly diagnosed MM patients and new combinations under evaluation, focusing on the efficacy and safety of these regimens and on open issues regarding the choice of therapy for elderly patients.